Solid fuel blending : principles, practices, and problems - 442862 Tillman, David A.; Duong, Dao (Dao N.B.); Harding, N. S. (Oxford, ENK. ; Waltham, MA : Elsevier, Butterworth-Heinemann)
Includes bibliographical references and index.